SOA service reuse by design - Dan, Asit; Johnson, Robert D; Carrato, Tony (International Conference on Software Engineering 2008, 2008)
Reuse of services in supporting new business processes, in addition to alignment of IT with business functions, is a key motivation in using Service-oriented Architecture (SOA) for developing business solutions. The three key benefits of service reuse are improving agility of solutions by quickly assembling new business processes from existing services to meet changing marketplace needs, reduction of cost by not just avoiding duplication of code for enabling similar business functions across multiple business processes, but also throughout the SOA life-cycle spanning service deployment and management, and also reducing risks by reusing well-tested code and runtime environments. However, currently there are many organizational challenges and lack of accepted SOA solution development methodologies and supporting technical capabilities in customer environments in achieving service reuse. This paper details the key challenges in achieving service reuse, and advocates taking a pro-active position in addressing these challenges by putting in place governing key aspects of service life-cycle and supporting technical capabilities.